Experiences in math for young children - Charlesworth, Rosalind (b)
This text focuses on the developmental sequence of mathematics for young children and its integration with other parts of the curriculum. For each math concept presented, the author explains how it might be incorporated into music and movement, language and visual arts, science, and social students for children from birth through age eight. Problem solving is promoted as the major means for constructing concepts with a balance of naturalistic, informal, and structured activities. The content is compatible with national standards and guidelines, giving educators the tools they need to prepare children to meet these standards. Each concept unit contains assessment, instructional, and evaluation strategies that educators can employ immediately. Further resources include active approaches to mathematics, resources for establishing learning centers, guidance on parental involvement, lists of children?s books with math concepts, and related Web sites.
Includes index.
Keywords: Mathematics Study and teaching (Primary).; Mathematics Study and teaching (Preschool).